(untitled) (Scientific journal of the Fergana State University, 2023)
The elemental composition of plum fruits and kernels of the stones was studied by mass spectrometry with inductively coupled plasma. The content of 43 macro- and microelements was analyzed in the studied plant samples. The results of the experiments showed that there are 25 elements in the fruits in the amount of 0.001-1296.280 mg/l, and in the kernels of the stones there are 40 elements in the amount of 0.001-7643.454 mg/l. The total amount of elements in the fruits is 2532.406 mg/l, in the kernels of the stones 11466.952 mg/l. Plum kernels of the stones contain 4.53 times more macro- and microelements than fruits. In the fruits and kernels of plum stones, such macroelements as Ca, K, Na, Mg, S were found. The amount of macroelements in fruits is 95.3% of the total content of minerals; and in the nuclei of the bones 97.2%. Plum fruits contain significant amounts of trace elements Al, Fe, Si, B, Mn, and in its kernels of stones Al, Fe, Si, Zn, B, Zn, Sr, Ba, Ti, Mn, Ni, V and Rb. The fruits contain the largest amount of aluminum, and the kernels kernels of the stones of iron. Lead and cadmium were found among the toxic elements in the fruits, and lead, cadmium, arsenic and mercury were found in the kernels of the stones. Among the toxic elements, lead has the largest amount, its content in the fruits is 0.744 mg/l, in the kernels of the stones 0.419 mg/l